Novel multi-scale cementitious composites developed using Microcrystalline Cellulose (MCC) and sisal fibers - de Souza Filho, Aloysio Gomes (2019)
In this work, multi-scale cementitious composites were developed using microcrystalline cellulose (MCC) and sisal fibers as reinforcements. Mechanical performance of plain mortar and reinforced mortar samples containing MCC (0.1, 0.2, 0.4 and 0.6%) and 0.50% sisal fibers (with respect to cement weight) was investigated. The experimental work was carried out by dispersing MCC in water with the help of a non-ionic surfactant (Pluronic F-127) using ultrasonication energy. The aqueous suspensions of MCC were then added to the cement-sand mixture along with sisal fibers. The developed cementitious composites were cured inside water for two different hydration periods, 28 and 56 days. It was observed that the fracture energy of the cementitious composites increased by 95% and 24%, respectively after 28 days and 56 days of hydration using 0.1% MCC and 0.5% sisal fibre